The National Institute for Health Research Critical Care Research Priority Setting Survey 2018 - Tatham,KC; McAuley,DF; Borthwick,M; Henderson,N; Bashevoy,G; Brett,SJ (Journal of the Intensive Care Society, 2020)
IntroductionDefining research priorities in intensive care is key todetermining appropriate allocation of funding. Several topics were identified from the recent James Lind Alliance (JLA) priority setting exerciseconducted with the Intensive Care Society(1). The JLA process included significant (and vital) patient/public contribution, but as a result may have failedto identify potential early-stage translational research topics, which are more likely identified by medical/academic members of relevant specialist intensive care groups. Theobjectiveof the present project was to complement the JLA project by generating an updated list of research prioritiesby facilitatingacademic research input.MethodAsurveywas conducted by the National Institute forHealth Research(NIHR)to identify the key research priorities from Intensive Care clinicians, including allied health professionals and academics, along with any evolving themes arising from translational research. Feasibility of all identified topics were then discussedand allocated to themesby ajoint clinical academics/NIHR focus group. ResultsThe survey was completed by 94 intensive care clinicians(including subspecialists),academicsand allied healthprofessions. In total203researchquestionswere identified, with the top fivethemesfocusing on:appropriate case selection (e.g.who and when to treat; 24%), ventilation(7%), sepsis (6%), delirium (5%) and rehabilitation (5%). DiscussionUtilising a methodology distinct from thatemployed by the JLAprocess, from a broad spectrum of intensive care clinicians/scientists,enabled identification of a variety of priority research areas. These topics cannowinform not only the investigator-led researchagenda, but will alsobe considered in due course by the NIHR for potential future funding calls.